PENGARUH BUDAYA ORGANISASI DAN KEMAMPUAN PEGAWAI TERHADAP KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS POLOKARTO - Arum Ratnaningsih, Kharisma; Tri Haryanto, Aris; Suhita, Damayanti (JI@P, 2024)
This study aims to determine the effect of Organizational Culture and Employee Ability on the Quality of Health Services at the Polokarto Health Center, Polokarto District, Sukoharjo Regency. The type of research conducted is causal associative research with a quantitative approach. The population in this study were all people who received services from the Polokarto Health Center, Polokarto District, Sukoharjo Regency. Sampling using Incidental Sampling technique. The basis for this sampling uses the Lemeshow formula with a sample size of 96. The data collection methods used in the study were observation, lift/questionnaire, and documentation. The data analysis technique used is descriptive statistics, validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results concluded that Organizational Culture has a moderate effect on Health Service Quality and Employee Ability has a strong effect on Health Service Quality at the Polokarto Health Center, Polokarto District, Sukoharjo Regency. Organizational Culture and Employee Ability also have a positive and significant effect on the Quality of Health Services at the Polokarto Health Center, Polokarto District, Sukoharjo Regency. This is evidenced by the Fcount value of 65.574. When compared with the Ftable value of 3.083, then Fcount> Ftable. Meanwhile, the result of the coefficient of determination analysis is 0.570. This shows that 57% of the Service Quality variable can be explained by the Organizational Culture and Employee Ability variables.